2019
DOI: 10.1002/adma.201805697
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Delivery of Monoclonal Antibodies to the Central Nervous System for Brain Tumor Therapy

Abstract: As an essential component of immunotherapy, monoclonal antibodies (mAbs) have emerged as a class of powerful therapeutics for treatment of a broad range of diseases. For central nervous system (CNS) diseases, however, the efficacy remains limited due to their inability to enter the CNS. A platform technology is reported here that enables effective delivery of mAbs to the CNS for brain tumor therapy. This is achieved by encapsulating the mAbs within nanocapsules that contain choline and acetylcholine analogues;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 60 publications
2
87
0
Order By: Relevance
“…They also demonstrated that Ang2 peptide played a key role in the BBB penetrating by receptor-mediated transcytosis, as was reported in the previous studies [38]. The effect of EP-1 peptide to enhance BBB penetration might be due to the synergistic effect by adsorption-mediated transcytosis [44,45]. The enhanced BBB penetration of DOX encapsulated in the non-functionalized dendrimer might be due to the slightly positive charge on the dendrimer that could improve the adsorptionmediate transcytosis.…”
Section: In Vitro Evaluation Of the Bbb Penetration Of The Dual-targesupporting
confidence: 61%
See 2 more Smart Citations
“…They also demonstrated that Ang2 peptide played a key role in the BBB penetrating by receptor-mediated transcytosis, as was reported in the previous studies [38]. The effect of EP-1 peptide to enhance BBB penetration might be due to the synergistic effect by adsorption-mediated transcytosis [44,45]. The enhanced BBB penetration of DOX encapsulated in the non-functionalized dendrimer might be due to the slightly positive charge on the dendrimer that could improve the adsorptionmediate transcytosis.…”
Section: In Vitro Evaluation Of the Bbb Penetration Of The Dual-targesupporting
confidence: 61%
“…Therefore, nanocarriers were modified with various BBB-penetrating ligands to improve the receptor-mediated transcytosis and transporter-mediated transcytosis, which could enhance the ability of drug carriers across the BBB and deliver the therapeutic reagents into lesions without disrupting homeostasis and biological barriers [5]. Previous researches have determined several receptors and transporters for BBB penetrating by transcytosis, including low-density lipoprotein receptor-relative protein-1 (LRP1) [38,39], insulin receptor [40,41], transferrin receptor (TfR) [42,43], nicotinic acetylcholine receptor and choline transporter [44,45] and a short peptide (RVG29) derived from rabies virus [29,33]. Among these receptors, LRP1, a large multi-ligand endocytic receptor belonging to the low-density lipoprotein receptor family, has attracted wide interest in the therapy and diagnose of CNS disease.…”
Section: Ivyspringmentioning
confidence: 99%
See 1 more Smart Citation
“…Western Blot : The collagenase IV was pre‐added in to the culture medium of PC 9 and LN 229 cell at a concentration of 2 µg mL −1 . Then the WINNER‐Nimo, n‐WINNER‐Nimo, and free nimotuzumab was added respectively at a final concentration of 100 µg mL −1 according to literature . After 48 h, the related proteins were extracted and then separated by SDS‐PAGE gel.…”
Section: Methodsmentioning
confidence: 99%
“…In Vivo Antitumor Activity : When the tumor size reached ≈60 mm 3 , the mice were randomly divided into four groups (3 mice each group): 1) Control group: mice were intravenously injected with 200 µL of saline; 2) WINNER‐Nimo group: mice were intravenously injected with WINNER‐Nimo (nimotuzumab of 4.54 mg kg −1 ); 3) n‐WINNER‐Nimo group: mice were intravenously injected with n‐WINNER‐Nimo (nimotuzumab of 4.54 mg kg −1 ); and 4) nimotuzumab group: mice were intravenously injected with free nimotuzumab (nimotuzumab of 4.54 mg kg −1 ). The used dose of nimotuzumab was according to literature and in the range of suggested nimotuzumab dose for human (100–400 mg per time). The mice were intravenously administered every 3 days for 21 days.…”
Section: Methodsmentioning
confidence: 99%